Application of Carbon Nanotube-Based Materials as Interlayers in High-Performance Lithium-Sulfur Batteries: A Review - Wei, Huijie; Liu, Yong; Zhai, Xiaoliang; Wang, Fei; Ren, Xinyuan; Tao, Feng; Li, Tengfei; Wang, Guangxin; Ren, Fengzhang (Frontiers in Energy Research, 2020)
With the ever-increasing demands of electrochemical energy storage, lithium–sulfur (Li–S) batteries have drawn more attention because of their superior theoretical energy density and high specific capacity. However, practical applications of Li–S batteries suffer from problems such as low conductivity of sulfur and discharged products, severe polysulfide shuttling effect, and large volume change of sulfur during cycling, resulting in sluggish rate performance, and unsatisfactory cycle life. Various nanostructured carbon materials have been served as barrier layers to overcome these problems. In particular, carbon nanotubes (CNTs) with unique 1D nanostructure, have been introduced to Li–S batteries as the intermediate layers because of its superior flexibility, excellent electrical conductivity, and good chemical stability. Moreover, CNTs and CNTs-based barrier layers could also curb lithium polysulfides shuttling. In the minireview, we summarize recent works of CNTs-based materials as modifying interlayers for Li-S batteries. In addition, the strategies to enhance electrochemical performances of the batteries are summarized and discussed. Finally, the challenges and prospects for future research of CNTs-based materials as interlayer are proposed. We hope this review will be useful for designing and fabricating high-performance Li–S batteries and boost their practical applications.